Nutrient Release Performance of Starch Coated NPK Fertilizers and Their Effects on Corn Growth - Nur Izza Faiqotul Himmah; Gunawan Djajakirana; Darmawan Darmawan (Universitas Sebelas Maret, 2018)
One way to control or slow down the nutrient release rate from fertilizer is by coating technique. Nowadays the use of biodegradable coating materials for slow-release fertilizer (SRF) is preferable because of environmental issues. This research was aimed to make SRF using starches and cellulose as the coating materials and to test the release rate of the nutrients. Five kinds of starches (cassava, corn, sago, wheat, and glutinous rice) and carboxymethyl cellulose (CMC) were used as coating material for granulated NPK fertilizer. The coated fertilizers (NPK SRF) were tested for their leaching rate in the soil by percolation experiment. The results showed that the kind of starch used influenced the release rate of the NPK SRFs. The NPK SRF coated with sago starch exhibited slow release rate and low leached nutrients which also resulted in slow growth of corn plant, as expected of SRF. The use of starch and CMC as biodegradable coating materials in this research has a possibility to affect the microbial activity in the soil so that the nutrient release became faster than the uncoated NPK fertilizer.